“Olha, essa consciência política surge do agir!”: experiências e memórias de estudantes secundaristas que ocuparam escolas públicas (Uberlândia – MG, 2016-2019) - Fávero, Douglas Gonsalves (2021)
The present research aimed to analyze the process of consciousness formation and the memory of high school students who occupied schools in Uberlândia between October and November 2016. We understand the process of consciousness formation from the perspective of Marx and Engels of becoming conscious a conflict and bringing it to an end through a political struggle. In the same theoretical perspective, we see memory as a set of representations and interpretations of this process, but mediated by determinations – in the sense of limits and pressures – of the present and future expectations and aspirations, creating a field of possibilities and disputes. To apprehend these subjective dimensions, we use the theoretical and methodological perspective of experience, indicated by E. P. Thompson, and of oral history as a research methodology, especially the perspectives developed by Alessandro Portelli. In this sense, we understood that the occupations were inserted and constituted as class relations, because, in addition to the claims against PEC 241 (55), the High School Reform and the School Without Party, there was a whole recognition of conflicts and antagonisms concerning a political and economic elite, a perception between them and us. In the same perspective, there was a dimension of direct confrontation with school authority and hierarchy and political relations with a set of working class organizations such as social movements, unions and political parties. In the meantime, the political action promoted by the students provided a set of understandings, albeit fragmented and diffuse form, of social relations, previously naturalized, such as class antagonisms involving, among others, the media, the State and the school itself. Thus, in the process of occupying the school and building a collective and democratic self-management, students began to glimpse the hierarchical and power relations that cross the school and its state and class character. These conceptions permeate school management, the educational environment and the curriculum. In this criticism, the students aimed, as a prefigurative moment, a public school, as a direct antithesis to the state school, placing them at the center of the educational process and decision-making within the administrative and pedagogical management scope. Still, we find a sense of incompleteness with the return to school normality, since the hegemony of the state school was reestablished. However, the relations between the subjects were substantially transformed because the construction and participation in the movement of occupations promoted, in several aspects, a profound educational process. Finally, we find a memory marked by a conflict between the greatness and enthusiasm of a significant political movement facing a conservative advance that limits the possibilities of radicalized protests, as are occupations in their various forms.